2019
DOI: 10.1093/hropen/hoz020
|View full text |Cite
|
Sign up to set email alerts
|

Secondary sex ratio in assisted reproduction: an analysis of 1 376 454 treatment cycles performed in the UK

Abstract: STUDY QUESTION Does ART impact the secondary sex ratio (SSR) when compared to natural conception? SUMMARY ANSWER IVF and ICSI as well as the stage of embryo transfer does impact the overall SSR. WHAT IS KNOWN ALREADY The World Health Organization quotes SSR for natural conception to range between 103 and 110 males per 100 female births. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Thus, female embryos seemed more sensitive to the vitrification conditions, as skewed sex ratio towards male gender was detected at birth. This phenomenon has been well established among ART births, which has been related with abnormal inactivation in one of the two X chromosomes in females and a higher rate of irregular placentation that incurs higher mortality for female embryos [33][34][35][36]. However, in the field of embryo cryopreservation, information is limited and controversial, and changes in the sex ratio have been attributed to the grading criteria used, instead of to the cryopreservation procedure per se [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, female embryos seemed more sensitive to the vitrification conditions, as skewed sex ratio towards male gender was detected at birth. This phenomenon has been well established among ART births, which has been related with abnormal inactivation in one of the two X chromosomes in females and a higher rate of irregular placentation that incurs higher mortality for female embryos [33][34][35][36]. However, in the field of embryo cryopreservation, information is limited and controversial, and changes in the sex ratio have been attributed to the grading criteria used, instead of to the cryopreservation procedure per se [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…As far we know, the normal value of SSR is 51.22% [ 1 ]. Different from those of large sample studies, an analysis from the UK showed that the SSR of babies born through ART was 50.98% [ 11 ]. It was lower than the normal value and approximated to ours.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal age, maternal height, pre-pregnancy BMI, parity, conception method, and smoking status during pregnancy were considered potential confounding factors in the multivariate analysis. Although some studies have shown that sex selection may be influenced by environmental factors, such as the conception method 21 and maternal periconceptional smoking status 22 , there is a lack of studies on significant associations between maternal factors (such as maternal age, height, and BMI) and fetal sex. However, we considered that the adjustment of these factors was important as there is insufficient evidence showing that they are independent of fetal sex.…”
Section: Methodsmentioning
confidence: 99%